2004
DOI: 10.1038/sj.cdd.4401365
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-induced neuronal cell death is mediated by the endoplasmic reticulum stress pathway involving CHOP

Abstract: Brain ischemia induces apoptosis in neuronal cells, but the mechanism is not well understood. When wild-type mice were subjected to bilateral common carotid arteries occlusion (BCCAO) for 15 min, apoptosis-associated morphological changes and appearance of TUNEL-positive cells were observed in the striatum and in the hippocampus at 48 h after occlusion. RT-PCR analysis revealed that mRNAs for ER stress-associated proapoptotic factor CHOP and an ER chaperone BiP are markedly induced at 12 h after BCCAO. Immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
299
3
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 388 publications
(319 citation statements)
references
References 46 publications
(52 reference statements)
15
299
3
2
Order By: Relevance
“…97 However, concerning the role of presenilin-1 in the ER stress pathway, the question of whether or not presenilin-1 mutations downregulate induction of BiP and CHOP is still being debated. 98,99 Therefore, it remains to be studied whether CHOP induction and ER stress-mediated apoptosis occur in the development of Alzheimer's disease. Several studies indicate that oxidative damages may have an important role in the development of Parkinson's disease.…”
Section: Neurodegenerative Diseasementioning
confidence: 99%
“…97 However, concerning the role of presenilin-1 in the ER stress pathway, the question of whether or not presenilin-1 mutations downregulate induction of BiP and CHOP is still being debated. 98,99 Therefore, it remains to be studied whether CHOP induction and ER stress-mediated apoptosis occur in the development of Alzheimer's disease. Several studies indicate that oxidative damages may have an important role in the development of Parkinson's disease.…”
Section: Neurodegenerative Diseasementioning
confidence: 99%
“…66 It has been reported that hippocampal neurons from CHOP/Gadd153-deficient mice are more resistant to cell death induced by hypoxia-reoxygenation compared with controls. 67 Fewer neurons degenerated in the CHOPÀ/À mice after ischemia, suggesting an important role for ER stress in ischemia/stroke. In brain trauma, caspase-12 is activated as a consequence of ER stress.…”
Section: Er Stress and Acute Neurodegenerationmentioning
confidence: 99%
“…8 However, activation of AKT by oxidative stress may facilitate cell death depending on context, 9 indicating that dynamic phosphorylation of AKT may affect several mechanisms related to cell fate. Proteostasis defects after brain ischemia are well documented, including disruption of the ubiquitin-proteasome system (UPS), 10 endoplasmic reticulum (ER) stress, 11,12 and inhibition of global protein synthesis mediated by the phosphorylation of eukaryotic initiation factor-2a (eIF2a) at serine 51 (Ser51). 13 These findings suggest that modulation of key components related to integrity of the proteome may promote neuroprotection after an ischemic insult.…”
Section: Introductionmentioning
confidence: 99%